(untitled) (International Journal of Engineering and Computer Science, 2015)
Due to the ease of network connectivity and the proliferation of digital capture devices, the access and sharing of images has become extremely feasible and convenient. However, some access and sharing may be unauthorized or illegal. Thus, digital watermarking has become an active research area focused on battling these types of activities. The paper compiles the various researches/advancements done in this field.